(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
CS was first proposed by Xin-She Yang and Suash Deb in 2009, and it has received a lot of interest because of its potential efficiency in handling a variety of optimisation issues and contributes substantial. Because of the publication of a large number of studies in the previous several years about cuckoo search, the body here you will find a summary of the majority of the research on cuckoo search that has been published in peer-reviewed publications a thorough classification of these references into relevant categories might provide a basis for subsequent study. Many studies on cuckoo search have been published in recent years, and the field on the subject has grown substantially. EAs’ main purpose is to find the internationally optimum or near-optimal solutions in the lowest amount of time. This section summarizes the majority of the particle swarm optimization investigations that have been published in consensus journals and at conventions so far. These resources may be organized into appropriate sections and used as a jumping off location for further research.